Speciation of pelagic zooplankton: Invisible boundaries can drive isolation of oceanic ctenophores - Johnson, Shannon B.; Winnikoff, Jacob R.; Schultz, Darrin T.; Christianson, Lynne M.; Patry, Wyatt L.; Mills, Claudia E.; Haddock, Steven H. D. (Frontiers in Genetics, 2022)
The study of evolution and speciation in non-model systems provides us with an opportunity to expand our understanding of biodiversity in nature. Connectivity studies generally focus on species with obvious boundaries to gene flow, but in open-ocean environments, such boundaries are difficult to identify. Due to the lack of obvious boundaries, speciation and population subdivision in the pelagic environment remain largely unexplained. Comb jellies (Phylum Ctenophora) are mostly planktonic gelatinous invertebrates, many of which are considered to have freely interbreeding distributions worldwide. It is thought that the lobate ctenophore, Bolinopsis infundibulum is distributed throughout cooler northern latitudes and B. vitrea warmer. Here, we examined the global population structure for species of Bolinopsis with genetic and morphological data. We found distinct evolutionary patterns within the genus, where B. infundibulum had a broad distribution from northern Pacific to Atlantic waters despite many physical barriers, while other species were geographically segregated despite few barriers. Divergent patterns of speciation within the genus suggest that oceanic currents, sea-level, and geological changes over time can act as either barriers or aids to dispersal in the pelagic environment. Further, we used population genomic data to examine evolution in the open ocean of a distinct lineage of Bolinopsis ctenophores from the North Eastern Pacific. Genetic information and morphological observations validated this as a separate species, Bolinopsis microptera, which was previously described but has recently been called B. infundibulum. We found that populations of B. microptera from California were in cytonuclear discordance, which indicates a secondary contact zone for previously isolated populations. Discordance at this scale is rare, especially in a continuous setting.